Novel therapeutics in myeloproliferative neoplasms - Sangeetha Venugopal; John Mascarenhas (Journal of Hematology & Oncology, 2020)
Abstract Hyperactive signaling of the Janus-Associated Kinase/Signal Transducers and Activators of Transcription (JAK/STAT) pathway is central to the pathogenesis of Philadelphia-chromosome-negative myeloproliferative neoplasms (MPN), i.e., polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) which are characterized by inherent biological and clinical heterogeneity. Patients with MPNs suffer from substantial symptom burden and curtailed longevity due to thrombohemorrhagic complications or progression to myelofibrosis or acute myeloid leukemia. Therefore, the management strategies focus on thrombosis risk mitigation in PV/ET, alleviation of symptom burden and improvement in cytopenias and red blood cell transfusion requirements, and disease course alteration in PMF. The United States Food and Drug Administration’s (USFDA) approval of two JAK inhibitors (ruxolitinib, fedratinib) has transformed the therapeutic landscape of MPNs in assuaging the need for frequent therapeutic phlebotomy (PV) and reduction in spleen and symptom burden (PV and PMF). Despite improving biological understanding of these complex clonal hematopoietic stem/progenitor cell neoplasms, none of the currently available therapies appear to modify the proclivity of the disease per se, thereby remaining an urgent unmet clinical need and an ongoing area of intense clinical investigation. This review will highlight the evolving targeted therapeutic agents that are in early- and late-stage MPN clinical development.